Efficacy of Exosome Adipose-Derived Stem Cells (ACSs-Exosome) on Skin Flaps Transplantation in Plastic Surgery: A Systematic Literature Review - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2022)
Background: Exosomes are a small subset of extracellular vesicles with a size of about 50 nm – 200 nm, which are found in many body fluids. The exosome is rich in various proteins and is a cargo that carries out the process of transporting and transporting between cells in the context of cell communication. This becomes a potential new therapeutic modality in triggering the modulation and activity of target cells so that ACSs-Exosome becomes a new potential to modulate skin flap transplantation repair in plastic surgery. Methods: The literature search process was carried out in various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the use of ASCs-exosome in skin flap transplantation repair in plastic surgery cases. Results: A total of 5 studies were included in this systematic review. In general, ASCs-exosome administration was more effective in the percentage of flap survival area than in the placebo group. There are 3 studies that state that the effectiveness of flap area survival is more than 70 percent compared to the placebo group, which is only in the range of 30-40 percent. Conclusion: ASCs-exosome has the potential to be developed to improve the survival rate of skin flap transplantation in the case of plastic surgery.